Serum amyloid A: an ozone‐induced circulating factor with potentially important functions in the lung‐brain axis. Issue 9 (19th September 2017) - Erickson, Michelle A.; Jude, Joseph; Zhao, Hengjiang; Rhea, Elizabeth M.; Salameh, Therese S.; Jester, William; Pu, Shelley; Harrowitz, Jenna; Nguyen, Ngan; Banks, William A.; Panettieri, Reynold A.; Jordan‐Sciutto, Kelly L.
ABSTRACT: Accumulating evidence suggests that O3 exposure may contribute to CNS dysfunction. Here, we posit that inflammatory and acute‐phase proteins in the circulation increase after O3 exposure and systemically convey signals of O3 exposure to the CNS. To model acute O3 exposure, female Balb/c mice were exposed to 3 ppm O3 or forced air for 2 h and were studied after 6 or 24 h. Of 23 cytokines and chemokines, only KC/CXCL1 was increased in blood 6 h after O3 exposure. The acute‐phase protein serum amyloid A (A‐SAA) was significantly increased by 24 h, whereas C‐reactive protein was unchanged. A‐SAA in blood correlated with total leukocytes, macrophages, and neutrophils in bronchoalveolar lavage from O3 ‐exposed mice. A‐SAA mRNA and protein were increased in the liver. We found that both isoforms of A‐SAA completely crossed the intact blood‐brain barrier, although the rate of SAA2.1 influx was approximately 5 times faster than that of SAA1.1. Finally, A‐SAA protein, but not mRNA, was increased in the CNS 24 h post‐O3 exposure. Our findings suggest that A‐SAA is functionally linked to pulmonary inflammation in our O3 exposure model and that A‐SAA could be an important systemic signal of O3 exposure to the CNS.—Erickson, M. A., Jude, J., Zhao, H., Rhea, E. M., Salameh, T. S., Jester, W., Pu, S., Harrowitz, J., Nguyen, N., Banks, W. A., Panettieri, R. A., Jr., Jordan‐Sciutto, K. L. Serum amyloid A: an ozone‐induced circulating factor with potentially important functions in the lung‐brain axis. FASEB J. 31, 3950–3965 (2017). www.fasebj.org —Erickson, Michelle A., Jude, Joseph, Zhao, Hengjiang, Rhea, Elizabeth M., Salameh, Therese S., Jester, William, Pu, Shelley, Harrowitz, Jenna, Nguyen, Ngan, Banks, William A., PanettieriJr., Reynold A., Jordan‐Sciutto, Kelly L. Serum amyloid A: an ozone‐induced circulating factor with potentially important functions in the lung‐brain axis. FASEB J. 31, 3950–3965 (2017)